Synergic effect of cellulose and lignin nanostructures in PLA based systems for food antibacterial packaging. (June 2016) - Yang, W.; Fortunati, E.; Dominici, F.; Giovanale, G.; Mazzaglia, A.; Balestra, G.M.; Kenny, J.M.; Puglia, D.
Graphical abstract: Highlights: Ternary poly(lactic acid) (PLA) based nanocomposites were successfully produced. Cellulose (CNC) and lignin (LNP) nanostructures were combined in PLA or graft-PLA. A synergic effect of LNP and CNC on UV light blocking capability was detected. The combination of LNP and CNC was effective in nucleation and crystal growth. LNP and CNC induced an antibacterial activity against Pst tomato pathogen. Abstract: Ternary polymeric films based on poly (lactic acid), obtained dispersing cellulose nanocrystals (CNC) and lignin nanoparticles (LNP) at two different amounts (1 and 3 wt%), respectively in neat PLA and glycidyl methacrylate (GMA) grafted PLA (g-PLA), were produced by melt extrusion. Thermal, optical and mechanical properties, as well as the morphologies of CNC and LNP reinforced PLA nanocomposites, were investigated. Results from UV–Vis characterization have confirmed a synergic effect of LNP and CNC based nanostructures in terms of transparency and UV light blocking capability. In addition, the combination of the two lignocellulosic nanofillers proved to be effective also in nucleation and crystal growth, with increased cristallinity values for ternary systems in comparison with binary nanocomposites. Furthermore, the ternary nanocomposites showed both higher strength and modulus values than those of neat PLA and PLA binary systems. Lignin nanoparticles and cellulose nanocrystals, when combined with neat or grafted poly (lactic acid), have shown antibacterial activity with reduction in multiplication of the bacterial plant pathogen Pseudomonas syringae pv. tomato (Pst). In particular, results from PLA nanocomposite films containing lignin nanoparticles pointed out how this green functionality allows to develop innovative strategies, towards harmful pathogens, helpful in the food packaging sector.